2022
DOI: 10.1007/s00414-022-02793-2
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem CT pulmonary findings in SARS-CoV-2-positive cases: correlation with lung histopathological findings and autopsy results

Abstract: Introduction/purpose Postmortem computed tomography (PMCT) is a valuable tool for analyzing the death of patients with SARS-CoV-2 infection. The purpose of this study was to investigate the correlation between PMCT lung findings in autopsy cadavers positive for SARS-CoV-2 infection and the severity of COVID-19 lung disease by histopathological analysis. Materials and methodsWe reviewed chest PMCT findings, paying particular attention to the lung parenchyma, in 8 autopsy cases positive for SARS-CoV-2. Correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 45 publications
2
31
0
Order By: Relevance
“…[ 23 , 29 , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] ]. The results of our systematic review are reported in Table I in chronological sequence.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 23 , 29 , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] ]. The results of our systematic review are reported in Table I in chronological sequence.…”
Section: Resultsmentioning
confidence: 99%
“…From the 20 papers, information about 515 cases with SARS-CoV-2 Real-time PCR (RTPCR) positivity and examined through PMCT were available. Seventeen papers [ 29 , [31] , [32] , [33] , [34] , [35] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [46] , [47] , [48] ] provided detailed information about cases. All cases regarded adults.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This autopsy was carried out on 14 February 2020 in Spain [ 91 ]. In Italy, the more recent autoptic examination on COVID-19 cadavers reported in February 2022 on eight cases (five males, three females) showed microthrombi formation and interstitial lymphocytic infiltrates [ 92 ]. Another Italian group examined 29 autopsies on COVID-19 deaths from October 2020 to February 2021, of which 21 patients died in hospitals and 7 outside; they did not report any anatomopathological findings, simply that those cadavers were SARS-CoV-2-positive at a swab test and how much [ 93 ].…”
Section: Before Going To Hospitals: How Can Positive Patients Residen...mentioning
confidence: 99%